Characteristics of Egg Roll Product with Treatment Proportions of Kimpul-Mung Bean Composite Flour: - - Puspitasari, Diana; Noerhartati, Endang; Mujianto (2477 - 6165, 2024)
Kimpul has potential raw material for egg rolls. The limitation is low protein which can be overcome by adding high protein ingredients, which is green beans (Vigna radiata). This research aims to find egg roll formulations and determine their characteristics. The research using a completely randomized factorial design. The test parameters are yield, proximate tests (water, ash, fat, protein, carbohydrates), and sensory tests (color, aroma, taste and texture). Parametric data was analyzed using analysis of variance (ANOVA). If the ANOVA test show real difference (significance < BNT 5%), then continue with Least Significant Difference test. Ordinal data from sensory tests were analyzed using Friedman Test, and descriptive analysis. The results showed that treatment interaction had no significant effect on the yield, water, carbohydrate, ash, fat, and protein content, but had a single significant effect on the yield. The treatment of the proportion of kimpul composite flour and green bean flour had a single significant effect on water content. The results of Friedman test showed that treatment proportion of kimpul composite flour and green bean flour with eggs addition had a significant effect on aroma, but had no significant effect on color, texture and taste of egg rolls. ​